Gambaran kualitas hidup pasien lansia pengguna gigi tiruan lepasan di RSGM Unpad - Cindy Annisa Melati; Sri Susilawati; Rasmi Rikmasari (Faculty of Dentistry, Universitas Gadjah Mada, 2017)
Description of quality of life on elderly patients with removable denture at RSGM Unpad. The elderlies are prone to the process of the gradual decreasing ability of the tissue for self-healing. This process greatly affects the dental structure and periodontal tissue leading to tooth decay. When it is not properly treated, it may disturb oral functions and activities influencing their life quality. This research, therefore, aims to obtain the description of quality of life on elderly patients with removable denture at the Prosthodontic Clinic RSGM Unpad. Research was conducted with a descriptive method using the consecutive technique sampling method. Data were collected from 31 elderly patients with removable denture at the Prosthodontic Clinic RSGM Unpad and quality of life was measured by GOHAI questionnaire. The results showed that the dimensions of physical function fell into the adequate criteria, while the dimensions of pain and inconvenience and psychosocial aspects were considered good. It can be concluded that the general quality of life on elderly patients with removable denture at the Prosthodontic Clinic RSGM Unpad were good. ABSTRAKPada lansia terjadi suatu proses menghilangnya secara perlahan kemampuan jaringan untuk memperbaiki diri yang disebut proses menua. Proses tersebut berpengaruh terhadap gigi dan jaringan periodontal sehingga mengakibatkan kehilangan gigi. Jika kehilangan gigi tidak diberi perawatan dapat mengganggu fungsi dan aktivitas rongga mulut sehingga akan mempunyaidampak pada kualitas hidupnya. Penelitian ini bertujuan untuk mengetahui gambaran kualitas hidup pasien lansia pengguna gigi tiruan lepasan di Instalasi Prostodonsia RSGM Unpad. Jenis penelitian adalah deksriptif dengan teknik pengambilan sampel menggunakan teknik populasi terjangkau dengan minimal sampling. Data dikumpulkan dari 31 pasien lansia pengguna gigi tiruan lepasan di Instalasi Prostodonsia RSGM Unpad. Kualitas hidup diukur dengan menggunakan kuesioner GOHAI. Hasil penelitian menunjukkan bahwa dimensi fungsi fisik berada pada kriteria cukup, dimensi nyeri dan ketidaknyamanan berada pada kriteria baik dan dimensi aspek psikososial berada pada kriteria baik. Kesimpulan penelitian menunjukkan kualitas hidup pasien lansia pengguna gigi tiruan lepasan di Instalasi Prostodonsia RSGM Unpad dikategorikan baik.